Life and bladder cancer: protocol for a longitudinal and cross-sectional patient-reported outcomes study of Yorkshire (UK) patients. Issue 6 (17th June 2019) - Mason, Samantha J; Downing, Amy; Wright, Penny; Bottomley, Sarah E; Winterbottom, Andrew; Glaser, Adam W; Catto, James W F
Abstract : Introduction: Little is known about the impact of bladder cancer (BC) and its treatments on health-related quality of life (HRQL). To date, most work has been small in scale or restricted to subsets of patients. Life and bladder cancer is a cross-sectional and longitudinal study collecting patient-reported outcomes within two distinct cohorts. Methods and analysis: A longitudinal study will collect patient-reported outcomes at 3-monthly intervals from newly diagnosed patients. Eligible cases will be identified by recruiting hospitals and surveyed at baseline, 6, 9 and 12 months postdiagnosis to explore changes in outcomes over time. A separate cross-sectional cohort of patients diagnosed within the last 10 years across Yorkshire will be identified through cancer registration systems and surveyed once to explore longer-term HRQL in BC survivors. A comprehensive patient-reported outcome measure (PROM) has been developed using generic, cancer-specific and BC-specific instruments. The study will provide evidence about how useful these PROMs are in measuring BC patient HRQL. The outcome data will be linked with administrative health data (eg, treatment information from hospital data). Ethics and dissemination: The study has received the following approvals: Yorkshire and the Humber—South Yorkshire Research Ethics Committee (17/YH/0095), Health Research Authority Confidentiality Advisory Group (17/CAG/0054). Results will be made available to patients, funders, NHS Trusts, Clinical Commissioning Groups, Strategic Clinical Networks and other researchers.